Recent advances of covalent organic frameworks in lithium ion batteries. Issue 3 (9th December 2020) - Tong, Yifan; Wang, Xuehan; Zhang, Yi; Huang, Weiwei
Abstract : This review divides the active sites of COFs into four categories: carbonyl, phenyl, imine bonds and other groups, and introduces their applications in LIBs. Abstract : Covalent organic frameworks (COFs) are emerging porous polymer materials. They are characterized by functionalization of their surface chemical properties, and excellent physical and chemical stability. This review focuses on the advances of COFs in lithium ion batteries (LIBs) regarding the active sites and discusses the redox mechanisms of active sites. Furthermore, the modification methods of COFs as electrode materials are analyzed and summarized.